Edge Theoretic Extended Contractions and Their Applications - R. Rajagopalan; Ekta Tamrakar; Fahad. S. Alshammari; H. K. Pathak; Reny George (Journal of Function Spaces)
Edge theoretic extended contractions are introduced and coincidence point theorems and common fixed-point theorems are proved for such contraction mappings in a metric space endowed with a graph. As further applications, we have proved the existence of a solution of a nonlinear integral equation of Volterra type and given a suitable example in support of our result.